Characterization of fatty acid desaturase gene family in Glycine max and their expression patterns in seeds after Fusarium fujikuroi infection - Li, Xinyuan; Munir, Maira; Zeng, Weiying; Sun, Zudong; Chang, Xiaoli; Yang, Wenyu (Frontiers in Plant Science, 2025)
BackgroundThe family of membrane-bound fatty acid desaturase (FAD) genes play a vital role in plant growth, development, and stress responses. The seed-borne pathogen Fusarium fujikuroi causes seed decay disease during pre-harvest and post-harvest stages of soybean, leading to a significant reduction in yield and quality. Therefore, it is very meaningful to characterize the diversity and function of the GmFAD gene family in soybean and to elucidate their roles in seed resistance to F. fujikuroi.ResultsIn this study, 30 full-length GmFAD genes were identified from the soybean genome. A range of analysis was conducted to characterize gene and protein structures, chromosomal locations, conserved motif and conserved structural domains, and results showed that GmFAD genes were clustered into seven subfamilies (FAB2, ADS, SLD, DES, FAD6, FAD2, FAD3/7/8), which is also supported by phylogenetic analysis. The diversity and expansion of the GmFAD gene family were mainly caused by segmental duplication, and their encoding proteins were observed to locate in chloroplast or endoplasmic reticulum. The promoters of GmFAD genes contained a set of cis-acting elements in response to plant hormone, defense and stress, light, and plant growth and development, indicating these genes have the complex expression regulation and diverse functions. Gene ontology (GO) and KEGG enrichment pathway analyses showed that GmFAD genes were closely related to the biosynthesis and metabolism of lipid and unsaturated fatty acids (UFAs). In addition, the expression of GmFADs was significantly changed in soybean seeds when challenged by the seed decay pathogen F. fujikuroi. Specifically, GmFAB2.1/2.2, GmFAD3.3/3-2B/7-1//8-2, and GmFAD2.3/2.5 genes displayed distinct temporal expression patterns in the resistant ND25 and susceptible CX12, highlighting their potential roles in soybean resistance against F. fujikuroi infection.ConclusionOur findings contribute to a deeper understanding of the GmFAD gene family and their intricate roles in soybean resistance against the seed-borne pathogen F. fujikuroi. Moreover, several distinct genes provide valuable candidates for further application in soybean resistant breeding.